Empirical Investigation on Success Factors in Adapting Agile Methodology in Software Development at Public Organizations - Al Tamimi, Adel (2014)
Agile Methodology is an emerging approach in software development industry, it aims to offer IT professionals with an alternative approach for managing IT projects more realistically via a set of iterative and adaptive sequence of activities. Great number of firms start adapting agile methodology, and day after day researchers leverage the agile state-of-the-art methodology to a better position. The empirical study of this research study employed in a public utility organization (A), in Dubai. The research study aims to identify the key success factors that enable organization (A) in adapting agile project management methodology successfully, in order to operate day-to-day IT projects more effectively. Through the research study, we identify a group of nine key elements that influence the agile implementation, these nine elements categorized under two main enablers, the Organizational factors and People factors. We developed a group of hypotheses around the nine key elements to address research question. Survey-based methodology employed to gather data from the respondents, the survey distributed among project managers and project team members who practiced in IT projects, with a minimum of 2 years in service within the same organization. The quantitative analysis reveals that only 7 hypothesized elements have statistically significant relationship with ‘Success in Adapting Agile Methodology’, the key elements are Training and Learning, Team Size, Personal Characteristics, Decision Time, Corporate Culture, User Satisfaction, and Competency.